Efektivitas Penggunaan Video 3d “Cerita Rakyat Bengkulu” Berbantuan Artificial Intelligence untuk Meningkatkan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun - Dwi Lyna Sari; Dwi Ismawati; Lina Eka Retnaningsih (JCE (Journal of Childhood Education), 2024)
This research aims to assess the effectiveness of using 3D video "Cerita Rakyat Bengkulu" assisted by artificial intelligence to enhance the socio-emotional skills of 5-6-year-old children in Bengkulu City. The study employed a quantitative experimental method using a Pre-experimental Design with a one-group pretest-posttest design. The sample consisted of 15 children from group B at PAUD IT Auladuna, comprising 7 boys and 8 girls. Data collection techniques included observation and documentation. Analytical methods involved effectiveness testing, normality testing, and statistical hypothesis testing. The normality test results showed significance values of 0.200 for pretest and 0.172 for posttest, both greater than (>) 0.05, indicating normal data distribution. The research findings indicate significant effectiveness of using 3D video "Cerita Rakyat Bengkulu" with artificial intelligence in improving the socio-emotional skills of group B children at PAUD IT Auladuna in the year 2023/2024. The socio-emotional skills significance value of 0.000 was less than (<) 0.05 (0.000 < 0.05), thereby rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). This suggests that the use of 3D video "Cerita Rakyat Bengkulu" assisted by artificial intelligence is effective in enhancing the socio-emotional skills of 5-6-year-old children at PAUD IT Auladuna in Bengkulu City.